Gastric regurgitation in patients undergoing gynecological laparoscopy with a laryngeal mask airway: a prospective observational study - Lemos, Jeconias; De Oliveira, Gildasio S.; de Pereira Cardoso, Hugo Eckner Dantas; Lemos, Lavínia Dantas Cardoso Neiva [UNESP]; de Carvalho, Lígia Raquel; Módolo, Norma Suely Pinheiro [UNESP] (Elsevier, 2017)
Objective The use of pneumoperitonium and the placement of patients in Trendelenburg position are commonly cited reasons for the potential development of intraoperative regurgitation of gastric contents and the need for an endotracheal tube in laparoscopic surgery. The main objective of the current investigation was to evaluate the presence of regurgitation of gastric contents in the oropharynx of patients having laparoscopic gynecological surgery with a laryngeal mask airway (LMA). Design Prospective, observational clinical investigation. Interventions Not applicable. Measurements Healthy subjects having a laparoscopic gynecological surgery under general anesthesia with a ProSeal LMA were included in the study. An insufflation pressure of 15 mm Hg was established as the maximum intra-abdominal pressure for the pneumoperitonium, and patients were placed in Trendelenburg position at a 15° angle. The pH of secretions extracted from subjects' hypopharynx was measured at multiple time points during the surgical procedure. A pH of oropharynx secretions ≤4.1 indicated the regurgitation of gastric contents. Main results Eighty subjects were recruited and completed the study. The median (range) of pH measurements at any time (T3-T9) was 6.5 (5.5-7.0). The median (range) for the lowest pH for each subject was 6.0 (5.5-7.0). The lowest detected pH in the hypopharynx was not correlated (Spearman ρ) with total surgical time (P = .9), total pneumopertitonium time (P = .17), or total Trendelenburg position time (P = .47). Conclusions Our current results suggest that the use of an LMA in healthy patients undergoing laparoscopic gynecological surgery may be safe. Future studies to confirm or refute our findings are warranted.
Keywords: Laparoscopy; LMA; Regurgitation